Enological chemistry - Moreno, Juan (Academic Press, 2012)
Enological Chemistry is written for the professional enologist tasked with finding the right balance of compounds to create or improve wine products. Related titles lack the appropriate focus for this audience, according to reviewers, failing either to be as comprehensive on the topic of chemistry, to include chemistry as part of the broader science of wine, or targeting a less scientific audience and including social and historical information not directly pertinent to the understanding of the role of chemistry in successful wine production. The topics in the book have been sequenced identically with the steps of the winemaking process. Thus, the book describes the most salient compounds involved in each vinification process, their properties and their balance; also, theoretical knowledge is matched with its practical application. The primary aim is to enable the reader to identify the specific compounds behind enological properties and processes, their chemical balance and their influence on the analytical and sensory quality of wine, as well as the physical, chemical and microbiological factors that affect their evolution during the winemaking process.